2019
DOI: 10.1111/jace.16393
|View full text |Cite
|
Sign up to set email alerts
|

3D microstructure and crack pathways of toughened CaO–Al2O3–SiO2 glass by precipitation of hexagonal CaAl2Si2O8 crystal

Abstract: We investigated CaO–Al2O3–SiO2 glass partially crystallized with molybdenum particles as nucleating agents. Microstructure of the material was characterized as a house‐of‐cards structure composed of plate‐like crystals. Microcracks propagated along the crystal plane parallel to the double layer of SiO4/AlO4 tetrahedrons separated by layers of calcium atoms. To investigate the fracture behavior of the hexagonal CaAl2Si2O8 crystals, molecular dynamics simulations were performed, which demonstrated that a crack c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 38 publications
4
34
0
Order By: Relevance
“…The fracture simulation has demonstrated that the crack cannot propagate along the notch direction, while the crystal specimen obviously shows slip dislocation along a calcium layer. 21 The same phenomenon is observed even in the glass/crystal composite model in this work.…”
Section: Crack Propagationsupporting
confidence: 84%
See 4 more Smart Citations
“…The fracture simulation has demonstrated that the crack cannot propagate along the notch direction, while the crystal specimen obviously shows slip dislocation along a calcium layer. 21 The same phenomenon is observed even in the glass/crystal composite model in this work.…”
Section: Crack Propagationsupporting
confidence: 84%
“…Composition of the SiO 2 -Al 2 O 3 -CaO parent glass experimentally studied is (SiO 2 ) 58.8 (Al 2 O 3 ) 12.6 (CaO ) 23.8 . 21 Assuming that 30% mole ratio of h-CAS is precipitated as experimentally measured, the glass matrix composition amounts to (SiO 2 ) 62.6 (Al 2 O 3 ) 7.3 (CaO) 30.1 . We firstly prepared a model for the glassy phase using the usual meltquench method described as follows: A random configuration of 25 003 atoms was melted at 3500 K for 500 ps and was subsequently cooled down monotonically to 300 K with a quenching rate of 1 K/ps.…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations